2001
DOI: 10.1054/bjoc.2000.1530
|View full text |Cite
|
Sign up to set email alerts
|

Germline TP53 alterations in Finnish breast cancer families are rare and occur at conserved mutation-prone sites

Abstract: SummaryWe have screened for germline TP53 mutations in Finnish BRCA1 and BRCA2 mutation-negative families. This study represents the largest survey of the entire protein-encoding portion of TP53, and indicates that mutations are only found at conserved domains in breast cancer families also meeting the criteria for Li-Fraumeni/Li-Fraumeni-like syndrome, explaining only a very small additional fraction of the hereditary breast cancer cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Consistent with our work, a few studies have reported several potential pathogenic mutations of p53 in individuals with evidence of hereditary susceptibility to breast cancer outside LFS and LFL families in different ethnic groups [3,[13][14][15][16][17][18][19], but almost all the identified variants showed to be single point missense mutations in contrast to a novel protein-truncated mutation identified in our population. Particularly, as the testing method used in our study, DHPLC has been confirmed to be a robust and sensitive screening technique [20].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our work, a few studies have reported several potential pathogenic mutations of p53 in individuals with evidence of hereditary susceptibility to breast cancer outside LFS and LFL families in different ethnic groups [3,[13][14][15][16][17][18][19], but almost all the identified variants showed to be single point missense mutations in contrast to a novel protein-truncated mutation identified in our population. Particularly, as the testing method used in our study, DHPLC has been confirmed to be a robust and sensitive screening technique [20].…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of mutation-positive families identified in our study is consistent with independent reports suggesting that germline TP53 mutations are rare in multiple case breast cancer families, possibly accounting for <1% of such families [25][26][27][28][29][30][31][32][34][35][36][37]. The higher frequency of mutation-positive families in our study is likely due to the selection criteria, which excluded BRCA1 and BRCA2 mutation-positive families.…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of TP53 germline mutations has been investigated in multiple studies [25][26][27][28][29][30][31][32], suggesting that they account for <1% of breast cancer families. However, the contribution of TP53 to breast cancer in the French Canadian population is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these mutations have also been reported in breast carcinomas. [36][37][38] EGFR/erbB-1 belongs to a receptor family with tyrosine kinase activity whose gene is located on chromosome 7p12. The EGFR signaling that mediates proliferation, migration, invasion, and suppression of apoptosis, can be blocked by a growing number of drug inhibitors.…”
mentioning
confidence: 99%